A new direct band gap silicon allotrope o-Si32 - Yang, Xin-Chao; Wei, Qun; Zhang, Mei-Guang; Hu, Ming-Wei; Li, Lin-Qian; Zhu, Xuan-Min (Chinese physics B, 2022)
Silicon is a preferred material in solar cells, and most of silicon allotropes have an indirect band gap. Therefore, it is important to find new direct band gap silicon. In the present work, a new direct band gap silicon allotrope of o -Si32 is discovered. The elastic constants, elastic anisotropy, phonon spectra, and electronic structure of o -Si32 are obtained using first-principles calculations. The results show that o -Si32 is mechanically and dynamically stable and is a direct semiconductor material with a band gap of 1.261 eV.